Shunt active power filter: a review on phase synchronization control techniques - Hoon, Yap; Mohd Radzi, Mohd Amran; Mohd Zainuri, Muhammad Ammirrul Atiqi; Md Zawawi, Mohamad Adzhar (MDPI, 2019)
Owing to the destructive impacts of harmonic currents, the topic of reducing their impacts on power system has attracted tremendous research interests. In this regard, a shunt active power filter (SAPF) is recognized to be the most reliable instrument. It performs by first detecting the harmonic currents that are present in a harmonic-contaminated power system, and subsequently generates and injects corrective mitigation current back into the power system to cancel out all the detected harmonic currents. This means that other than the ability to generate corrective mitigation current itself, it is actually more important to make sure that the SAPF is able to operate in phase with the operating power system, so that the mitigation current can correctly be injected. Hence, proper synchronization technique needs to be integrated when designing the control algorithms of SAPF. This paper critically discusses and analyzes various types of existing phase synchronization techniques which have been applied to manage operation of SAPF; in terms of features, working principle, implementation and performance. The analysis provided can potentially serve as a guideline and provision of information on selecting the most suitable technique for synchronizing SAPF with the connected power system.